2014
DOI: 10.1007/s00424-014-1582-3
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane channel-like (TMC) genes are required for auditory and vestibular mechanosensation

Abstract: Mutations of the transmembrane channel-like 1 (TMC1) gene can cause dominant and recessive forms of deafness in humans and mice. TMC1 is one of eight mammalian TMC genes of unknown function. The multi-pass transmembrane topologic structure of the proteins they encode suggests roles as a receptor, transporter, channel or pump. Tmc1 and the closely related Tmc2 gene are expressed in neurosensory hair cells of the auditory and vestibular end organs of the mouse inner ear. Recent studies have demonstrated that Tmc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
82
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 36 publications
7
82
0
Order By: Relevance
“…It remains to be shown whether TMC1 and TMC2 can yield channel activities in heterologous expression systems (52,53), and they likely require other proteins for their function in mechanotransduction (54)(55)(56). We have attempted to ectopically express the Drosophila tmc gene product in a variety of heterologous systems.…”
Section: Differential Functions Of Different Sensory Neurons In Regulmentioning
confidence: 99%
“…It remains to be shown whether TMC1 and TMC2 can yield channel activities in heterologous expression systems (52,53), and they likely require other proteins for their function in mechanotransduction (54)(55)(56). We have attempted to ectopically express the Drosophila tmc gene product in a variety of heterologous systems.…”
Section: Differential Functions Of Different Sensory Neurons In Regulmentioning
confidence: 99%
“…TMC proteins may act as ion channels, ion pumps, or transporters depending on their structure. Data obtained from the tmc1 mutant mice suggest a possible role for TMC1 in mechanoelectrical transduction of sound by cochlear hair cells (Kawashima et al, 2015). In their screening of 374 families, Ganapathy et al (2014) identified eight TMC1 mutations.…”
Section: Dfnb7/11/tmc1mentioning
confidence: 99%
“…Mutations in TMC1 have been linked to recessive and dominant genetic deafness 17 . A dominant-negative missense mutation in TMC1 (p.M418K, c.T1253A) causes reduced single-channel current levels and calcium permeability 16 and progressive post-lingual sensorineural hearing loss in humans 1820 . The Bth/+ mouse model carries the orthologous missense mutation (p.M412K, c.T1235A) in the mouse Tmc1 gene and exhibits progressive auditory response threshold elevation and progressive hair cell loss beginning at one month 21 .…”
mentioning
confidence: 99%